The Exploration of Self-Efficacy Beliefs and PCK among Gen Z Pre-Service Physics Teachers in Indonesia: A Sequential Explanatory Study - Ike Lusi Meilina; Singgih Bektiarso; Sayyidatun Najah; Ummi Qonitatin; Rosita Putri Rahmi Haerani (Universitas Negeri Semarang, 2026)
This study aims to explore the relationship between self-efficacy and Pedagogical Content Knowledge (PCK) of Generation Z preservice physics teachers. Given the unique characteristics of Generation Z, who are tech-savvy but often face challenges in mastering in-depth physics content. The research method used is a mixed method with a sequential explanatory design. Quantitative data were collected from 75 preservice physics teachers using a PCK test instrument adapted from DTAMS and a self-efficacy questionnaire. Qualitative data were obtained from in-depth interviews with 20 preservice teacher participants. The main finding of the quantitative analysis was that there was no significant relationship between self-efficacy and PCK among preservice teachers. Pearson's correlation test confirmed that there was no significant linear relationship between the two (r<0.2). Qualitative findings explain that self-efficacy is conditional, built through philosophical beliefs about the importance of learning reform, short-term preparation of physics material before teaching, and validation of the success of teaching methods during field practice. This study concludes that for Generation Z preservice physics teachers, self-efficacy develops independently of the domains of knowledge and pedagogy. The implication of this study is that teaching preparation and teaching practice strategies need to be trained more in the preparation of preservice teachers.